Toxic effects and mechanisms of nanoplastics and sulfonamide antibiotics on Scenedesmus obliquus - Jianyuan Yang; Zhen Yang; Jing Wang; Yanpeng Liang; Honghu Zeng; Litang Qin; Xiaohong Song; Lingyun Mo (Ecotoxicology and Environmental Safety)
The prevalence of nanoplastics (NPs) and sulfonamide antibiotics (SAs) in the aquatic environment is potentially harmful to the environment, and these pollutants are often present in the environment in the form of composite ones, thereby introducing more complex effects and hazards to the environment. Therefore, it is crucial to investigate the toxic effects of the individual target pollutants and their mixtures. In this study, we used Scenedesmus obliquus as the test organisms, two types of NPs: polystyrene (PS) and amine-modified (NH2-PS), four SAs: sulfapyridine (SPY), sulfamethazine (SMR), sulfamethoxypyridazine (SMP), and sulfamethoxazole (SMZ), and their eight binary mixtures were examined. We investigated the toxic interactions of the eight binary mixtures on Scenedesmus obliquus and assessed the impact of the 14 mixtures on the physiological and biochemical properties of Scenedesmus obliquus. Interaction of pollutant assemblages with algal cells observed using field emission scanning electron microscopy. The results showed that the six target pollutants and their eight binary mixtures were significantly toxic to Scenedesmus obliquus within 96 h. The toxicity of individual pollutants was in the order of SPY (EC50: 12.38 mg/L) > SMZ (EC50: 20.43 mg/L) > SMP (EC50: 32.96 mg/L) > SMR (EC50: 41.06 mg/L) > PS (EC50: 284.13 mg/L) > NH2-PS (EC50: 754.13 mg/L); the toxicity of binary mixtures composed of NPs and SAs (89.13 ∼ 1905.46 mg/L) was generally less toxic than that of unitary SAs (12.38 ∼ 41.06 mg/L). Suggesting that the presence of NPs reduced the toxicity of the SAs. The different types of NPs influenced the interaction and toxicity of the mixtures. The effects-based model deviation ratio method was used to quantitatively assess the interactions of the mixture systems in the 10∼90 % experimental effect range. The majority of the PS-containing mixtures exhibited antagonistic interactions. The interactions of NH2-PS-containing mixtures on Scenedesmus obliquus showed different interactions depending on the concentration ratios of the mixture components. The exposure of two NPs and four SAs and their binary mixtures differently promoted or inhibited superoxide dismutase and catalase activities in algal cells to different degrees and resulted in elevated levels of malondialdehyde content, suggesting that oxidative stress led to significant inhibition of chlorophyll content, total protein content, and growth of algal cells. The SEM image can be a more intuitive means of observing the interaction of nanoplastics with algal cells. These findings offer valuable data for the ecological risk assessment of NPs and SAs.